Association of cardiovascular events with glycosylated haemoglobin in diabetic patients - Deo, RK; Karki, P; Sharma, SK; Acharya, P (Kathmandu University Medical Journal, 2009)
Background: In persons with diabetes, chronic hyperglycemia (assessed by glycosylated hemoglobin level) is related to the development of microvascular disease; however, the relation of glycosylated hemoglobin (HbA1c) to macrovascular disease is less clear. Objective: To study the association of cardiovascular events (CVE) with glycosylated haemoglobin in diabetic patients. Design: Case control study Setting: B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal Materials and methods: Fifty diabetic patients with recent cardiovascular events: myocardial infarction (MI) or stroke was included in the study. There were 25 patients of myocardial infarction and 25 patients of stroke. Fifty diabetic patients without cardiovascular events were taken as control. Results: After adjustment for age, smoking, body mass index, systolic blood pressure and total cholesterol at baseline, level of HbA1c was statistically significant (p = 0.017) among patients with CVE. For MI, level of HbA1c was statistically significant (p = 0.018) while for stroke, level of HbA1c was not significant (p = 0.694). Mean blood glucose also predicted CVE and MI but not stroke in this study (p values = 0.006, 0.006 and 0.670 respectively). Fasting and postprandial plasma glucose was statistically significant in CVE (p values = 0.024 and 0.019 respectively). Urine protein was statistically significant for CVE, MI and stroke (p values = 0.000, 0.032, 0.032 and OR 4.571 (95% CI: 1.963- 10.646), 2.667 (95% CI: 1.043-6.815), 2.667 (95% CI: 1.043-6.815) respectively. Limitations: Sample size was limited due to time constraint and limited resources. Cases with peripheral artery disease were not included in the study. Conclusion: Glycosylated haemoglobin is associated with cardiovascular events and myocardial infarction but not stroke. Key words: Glycosylated Haemoglobin, Cardiovascular event, Myocardial infarction, Stroke doi: 10.3126/kumj.v6i4.1739 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 476-485